Allegories of "Postracial" Capitalism: Colson Whitehead and the Materials of Twenty-First-Century Black Cultural Authorship. Issue 4 (8th August 2019) - Bose, Maria
ABSTRACT: This essay reads novels by Colson Whitehead as sustained allegorical engagements with race's conceptual and discursive mutation across capitalism's historical development, and also as highly self-reflexive meditations on the novel of ethnicity's formal affinities with race's making and unmaking in the service of capital accumulation. Special attention is given to Whitehead's 2006 novel, Apex Hides the Hurt, which recounts the story of an African American "nomenclature consultant" tasked with rebranding an ex-slave town originally known for its barbed wire production but eager to attract the business of an up-and-coming software firm. An allegory for the changing technologies by which borders are controlled – from the material constraints of barbed wire to the "invisible" fiber optic wires that now mediate production on a global scale – I argue that Apex links labor abstractions wrought by digital post-Fordism's rise to race's remaking under neoliberal market logics of qualitative uniqueness. A coda examines how Apex 's preoccupation with the discourse of brand management yokes Whitehead's critique of "postracial" capitalism to questions of "postracial" novelistic practice similarly broached by Chimamanda Adichie, NoViolet Bulawayo, Teju Cole, Percival Everett, and Michael Thomas.